IDENTIFIKASI MELAYU DALAM PERSPEKTIF HISTORIS - Widjayengrono, Pheres Sunu (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2023)
This article attempts to show the meaning of Malay, especially in Riau Archipelago, in historical perspective with mean theoretical framework divided in three periods (modern, medieval, and classic periods). It’s study of intellectual history methodology and applies history method with using of related secondary sources. Comparative analysis and cultural approach’s applied to data interpretation so that useful for historical analysis. Each period has characteristic meaning depended on mentality situation and bias of ideas from previous period. This article assumes that each dominantly formal or governing power in each period is primary element and cause for cultural meaning and people’s acceptance of Malay definition. Keywords: Malay, ethnic, society, cultural, identification.